椭圆齿轮有限元模态分析 - 张宏文 (Jixie chuandong)
Fifth order natural frequency and modal shape of elliptical gear were obtained from the modal analysis of cosmosworks module in the finite element software. The effect of eccentricity on natural frequency and modal shape of elliptical gear was done a comparative analysis. The results show that eccentricity has a great influence on natural frequency of elliptical gear.